Prevalence of perioperative hypothermia and predisposing factors in a children's hospital - Murat Celal Sözbilen; Kübra Evren Şahin (Acta Medica Alanya)
Aim: Perioperative hypothermia is more common in pediatric patients than in adult patients due to increased body surface area/weight ratio and limited subcutaneous fat deposits. Therefore, active and passive warming techniques are used more frequently in the surgeries applied to pediatric patients. This study presents the prevalence of perioperative hypothermia and the predisposing conditions for perioperative hypothermia in pediatric orthopedic surgeries in which active and passive warming techniques are applied.Methods: This cross-sectional, descriptive, and observational study included 102 children admitted to the pediatric orthopedic clinic of a children’s hospital. Temperature measurements were made with a calibrated infrared tympanic thermometer in all cases while they were waiting in the service room, when they entered the operation theater, when they left the operation theater and when they left the postoperative care unit. Their demographic data, hemogram and thyroid hormone parameters, preoperative fasting times related to the procedure and temperature were recorded. Also, the humidity and temperature values of the operating theater, the operation type performed, the duration of the operation, the time spent in the operating theater and the recovery time from anesthesia, were all recorded in their follow-up forms. Data analysis was done using the SPSS V21.0 and was conducted at a 95% confidence interval.Results: Hypothermia was observed in 20.58% of 102 patients included in the study. Predisposing factors for perioperative hypothermia included the fact that the patient had a diagnosis of concomitant cerebral palsy, the patient's body temperature was low in the service area, low temperature and humidity values in the operating theatre and staying in the operating theatre for a prolonged period of time.Conclusion: Although active and passive warming techniques are applied during the operation, perioperative hypothermia was observed in 20.58% of pediatric patients who underwent the orthopedic operation. Consideration of predisposing factors together with active and passive warming techniques may reduce the incidence of perioperative hypothermia.